Free of plastic bags - Judi Wakhungu (Our Planet, 2018)
Kenya faces major challenges in waste management. Most urban centres lack basic waste management structures and open dumping is the most popular option. A close look at problematic waste at roadsides, rivers, dumpsites, and most public spaces revealed that polythene bags were most widespread. Scientists claim that polythene bags take over 1,000 years to decompose: hence the earliest ones are still with us somewhere in the environment.